Effective climate change adaptation means supporting community autonomy - Pisor, Anne C.; Basurto, Xavier; Douglass, Kristina G.; Mach, Katharine J.; Ready, Elspeth; Tylianakis, Jason M.; Hazel, Ashley; Kline, Michelle A.; Kramer, Karen L.; Lansing, J. Stephen; Moritz, Mark; Smaldino, Paul E.; et al. (Nature climate change, 2022)
Communities want to determine their own climate change adaptation strategies, and scientists and decision-makers should listen to them — both the equity and efficacy of climate change adaptation depend on it. We outline key lessons researchers and development actors can take to support communities and learn from them.